MEASUREMENT OF PRODUCTION PROCESS PRODUCTIVITY OF BOLT HEXAGON NUT M10 X 60MM WITH JUST IN TIME METHODS AND MANUFACTURING CYCLE EFFECTIVENESS (MCE) TO REDUCING NON VALUE ADDED ACTIVITY - Sari, Indah Apriliana; Septi W, Reynaldi; Darmadi (Tibuana, 2019)
The purpose of this research is to calculate the value of productivity carried out in the production of Bolt Hexagon Nut M10X 60MM that have applied the Just in Time method. Machine productivity calculations are carried out using Manufacturing Cycle Effectiveness (MCE) to reduce non-value-added processes. The results of research conducted from January to December 2017 showed an increase in the MCE value of 35%, and productivity increased by 139.75 kg / hour for one year. The calculation shows that MCE is very effective for use in planning and improving value-added activities.